2005
DOI: 10.1016/j.jvs.2005.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Brachiocephalic reconstruction II: Operative and endovascular management of single-vessel disease

Abstract: Operative bypass and endovascular intervention for single-vessel brachiocephalic disease are both associated with acceptably low operative morbidity and mortality. Operative bypass produces significantly better mid-term freedom from graft or intervention failure than endovascular intervention and produces excellent long-term freedom from failure. Endovascular intervention offers tangible benefits regarding cost, level of invasiveness, and subjective patient satisfaction. Undetermined are the differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 16 publications
2
30
1
1
Order By: Relevance
“…This is supported by other authors as well, such as Takach et al 13 who showed that CSBP produces excellent long-term patency and extended symptom relief, with acceptably low operative morbidity and mortality. According to the authors, operative bypass showed significantly better mid-term freedom from graft or intervention failure than endovascular intervention and produced excellent long-term freedom from failure.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is supported by other authors as well, such as Takach et al 13 who showed that CSBP produces excellent long-term patency and extended symptom relief, with acceptably low operative morbidity and mortality. According to the authors, operative bypass showed significantly better mid-term freedom from graft or intervention failure than endovascular intervention and produced excellent long-term freedom from failure.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, they underlined that the proven durability may offer (1) extended symptom relief to the relatively younger patient, (2) a survival advantage associated with preservation of internal mammary artery perfusion in patients at risk for myocardial revascularization, (3) optimal durability in patients requiring a concomitant open procedure, and (4) preservation of limb function in patients who require aortic endovascular graft placement. 13 Additionally, because of the documented superiority of prosthetic grafts compared with saphenous vein grafts, Dacron or PTFE was preferentially used in our study for CSBP. However, we used a venous graft in 5 patients because of anatomical and technical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Although most authors agree that success rate largely depends on severity, pathology, and location of the lesion; in general PTA gives comparable, if not better, results compared with conventional open surgery. 2,[31][32][33][34] Patients with hemodialysis access occlusion are the most extensively studied population in terms of use of PTA as primary intervention. Although multiple procedures may be needed, PTA showed promising results in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…The percutaneous approach has many theoretical advantages over open surgical repair including the ability to perform such procedures without the need for general anesthesia, quicker recovery times, shorter length of hospital stay and lower costs (Takach et al [22] reported a mean saving of $8787 per procedure [22]). High-risk patients such as those suffering cardiac events and others with significant comorbidities, previous cervical operations, or prior cervical irradiation are likely to benefit from an endovascular approach to innominate artery stenosis or occlusions.…”
Section: Resultsmentioning
confidence: 99%